Efficient Revenue Sharing and Upper Level Governments: Theory and Application to Germany - Thiess Buettner; Sebastian Hauptmeier; Robert Schwager (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2006)
Recent literature has emphasized that redistributive grant systems may tend to internalize fiscal externalities arising from tax competition. This paper further explores the conditions under which local grant systems enforced by the state government will enhance efficiency. A system of redistributive grants among governments is introduced into a standard model of tax competition. This basic model is then extended in order to allow for variations in the government objectives at the state level. A subsequent empirical analysis of local tax policy exploits the experience with local fiscal revenue sharing in Germany. The results suggest that attempts of state level governments to extract fiscal resources from the local revenue sharing system exert an upward pressure on tax rates.
Keywords: H77; H71; 330; Fiscal Equalization; Tax Competition Fiscal Federalism; Germany; Kommunaler Finanzausgleich; Steuerwettbewerb; Finanzföderalismus; Theorie; Deutschland